Optimalisasi Patroli Dialogis Guna Menurunkan Curanmor Oleh Satuan Sabhara Polres Sumedang - Avif Mulya Pratama (Police Studies Review, 2020)
Theft of a motor vehicle is an event that lately often appears in the midst of society. The patrol conducted by the police, especially the Sabhara Police Sumedang unit, aims to foster community participation in uniformed police in the community so that the presence of the police can be useful to prevent the occurrence of kamtibmas disruption and other crimes in the community. The purpose of this study was to determine the description of motor vehicle theft, to find out what optimizations were carried out by the dialogic patrol unit to reduce curanmor, and to determine what factors influenced the implementation of dialogic patrols to reduce the curanmor by the Sabhara Unit of the Sumedang District Police. This study uses qualitative methods with descriptive analysis techniques. The location of this research is in the jurisdiction of the Sumedang District Police. All data were collected by observation, interview and document study methods. The validity of the data is used triangulation of sources, techniques and time. Data were analyzed using data reduction, data presentation and conclusion drawing. The results of this study stated that the number of muranmor in the Sumedang district police jurisdiction indicated that in 2017 there were 151 events, in 2018 there were 223 events and the last in 2019 there were 113 events and it occurred in urban areas such as Jatinangor, North Sumedang, South Sumedang , Cimanggung, and Cimalakama. Obstacles that exist in the implementation of dialogical patrol activities namely patrol activities cannot be carried out properly without the existence of supporting facilities and infrastructure. Related to the fuel budget is still a problem related to the implementation of patrol activities. For human resources, there is still lack of knowledge on patrol. The implementation schedule is not yet in accordance with the implementation.